Material Welfare of the Population as a Factor of Economic Security (on Materials of the Republic of Mordovia) - Ludmila Nikokaevna Lipatova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article on the basis of the analysis of the main indicators of a standard of living material conditions of activity of the population of Russia are characterized, interregional distinctions come to light.